RELATIONSHIP OF ANEMIA INCIDENCE WITH NUTRITIONAL STATUS EXPERIENCED IN ADOLESCENTS IN YOGYAKARTA AREA - Mohamad Judha (Mikki: Majalah Ilmu Keperawatan dan Kesehatan Indonesia, 2020)
Background : Fulfillment of nutrition is very important so that growth and development take place perfectly . Adolescent girls are among the vulnerable groups suffering from anemia because teenage girls experience menstruation each month which causes iron loss. Objective : To determine the relationship of nutritional status with the incidence of anemia in adolescent girls at Junior high school in Yogyakarta.Research Methods :  The purpose of this research is to determine the relationship between nutritional status and anemia in adolecents. Population in this research are 235 students. To measure the health status used HB, measurement of body weight using a bathroom scales and microteise .  The sample used in this study was 70 people using purposive random sampling in junior high school.  Univarat data analysis and bivariate analysis using chi square .Results : The test results with Chi Square test resulted in a calculated Chi Square value of 1.322 with a significance value of p = 0.516. Because the value of p> 0,05 it can be concluded that there is no significant relationship between nutritional status with the incidence of anemia in young women.Conclusion : There is no correlation between nutritional status and the incidence of anemia in adolescent girls